Insular glioblastoma: surgical challenges, survival outcomes and prognostic factors. (2nd January 2023) - Singh, Amanjot; Das, Kuntal Kanti; Khatri, Deepak; Singh, Suyash; Gosal, Jaskaran Singh; Jaiswal, Sushila; Mishra, Prabhakar; Mehrotra, Anant; Bhaisora, Kamlesh; Sardhara, Jayesh; Srivastava, Arun Kumar; Jaiswal, Awadhesh; et al.
Abstract: Background: Insular gliomas are unique, challenging and evoke a lot of interest amongst neurosurgeons. Publications on insular glioma generally focus on the surgical intricacies and extent of resection pertaining to the low-grade gliomas. Insular glioblastomas (iGBM) have not been analysed separately before. Methods: Histologically proven WHO grade IV gliomas involving the insula over a 9-year period were studied. Their clinical presentation, radiological features, surgical findings and survival outcomes were assessed. Statistical methods were used to determine the favourable predictors of survival. Results: Out of 27 patients (M:F = 2.9:1), 18 (66%) patients had a tumour extension beyond the insula, 10 (37%) of whom had basal ganglia involvement. Total, near total and subtotal excisions were performed in 7 (26%), 9 (33%) and 11 (40.7%) patients, respectively. Twenty-three patients had glioblastoma, while four had gliosarcoma. IDH mutation was negative in six of the seven patients where it was done. Median overall survival was 5 months. Multivariate analysis showed that a female gender ( p = 0.013), seizures in the preoperative period ( p = 0.048) and completion of adjuvant therapy ( p = 0.003) were associated with a longer survival. Conclusion: Insular glioblastomas have a poor prognosis. Insular location and certain tumour characteristics often limit the extent of resection of iGBMs. Moreover, postoperative complications sometimes negate the advantages of a radical resection. A female gender, presentation with seizures and completion of adjuvant chemoradiotherapy appear to be good prognostic factors.